Phenotype plasticity and altered sensitivity to chemotherapeutic agents in aggressive prostate cancer cells - Paxson, Allan I.; Chang, Loren H.; Gard, Jaime M. C.; Harryman, William L.; Nelson, Colin S.; Salmon, Stella B.; Marr, Kendra D.; Wachsmuth, Leah M.; Ramanathan, Anita; Ran, Jing; Kapoor, Abhijeet; Marugan, Juan J.; et al. (Frontiers in Cell and Developmental Biology, 2023)
In 2023, approximately 288,300 new diagnoses of prostate cancer will occur, with 34,700 disease-related deaths. Death from prostate cancer is associated with metastasis, enabled by progression of tumor phenotypes and successful extracapsular extension to reach Batson’s venous plexus, a specific route to the spine and brain. Using a mouse-human tumor xenograft model, we isolated an aggressive muscle invasive cell population of prostate cancer, called DU145J7 with a distinct biophysical phenotype, elevated histone H3K27, and increased matrix metalloproteinase 14 expression as compared to the non-aggressive parent cell population called DU145WT. Our goal was to determine the sensitivities to known chemotherapeutic agents of the aggressive cells as compared to the parent population. High-throughput screening was performed with 5,578 compounds, comprising of approved and investigational drugs for oncology. Eleven compounds were selected for additional testing, which revealed that vorinostat, 5-azacitidine, and fimepinostat (epigenetic inhibitors) showed 2.6-to-7.5-fold increases in lethality for the aggressive prostate cancer cell population as compared to the parent, as judged by the concentration of drug to inhibit 50% cell growth (IC50). On the other hand, the DU145J7 cells were 2.2-to-4.0-fold resistant to mitoxantrone, daunorubicin, and gimatecan (topoisomerase inhibitors) as compared to DU145WT. No differences in sensitivities between cell populations were found for docetaxel or pirarubicin. The increased sensitivity of DU145J7 prostate cancer cells to chromatin modifying agents suggests a therapeutic vulnerability occurs after tumor cells invade into and through muscle. Future work will determine which epigenetic modifiers and what combinations will be most effective to eradicate early aggressive tumor populations.